Comparison of ethical reasoning in nursing students and nurses in - Zirak, mohammad; Mogadasian, sima; Abdullah-Zadeh, farahnaz; Rahmani, azad (Advances in Nursing & Midwifery, 2013)
Abstract Background and aim High ethical reasoning ability is one of the main requirements of nursing profession. This ethical reasoning should be improved in nursing student during educational period. It should be further evolved during their independent clinical work as a nurse. Limited evidences are exist about the level of ethical reasoning of nursing students and nurses in Iran. Therefore, the purpose of this study was to compare the ethical reasoning of nursing students and nurses in Tabriz University of Medical Sciences . Materials and Methods This descriptive-comparative study was performed on 115 nursing students and 269 nurses who were selected by census. Nursing Dilemma Test NDT questionnaire was used for data collection. It consists of 6 scenarios. Ethical reasoning score (Nursing Principled Thinking NP) was the sum of scores of fifth and sixth levels of Kohlberg ethical development questionnaire. The scores varied from 18 to 66. The data were analyzed using SPSS and by descriptive and inferential statistics. Findings Ethical reasoning score of nursing students (48.9±6.5; mean±SD) was significantly higher than the score of nurses (46.6±6.7) (p=0.02). Also it was found that NP scores of nurses working in medical wards are significantly higher than scores of other wards nurses (p=0.02). NP scores were declined by increasing of clinical experience (p= 0.04). Conclusion Lower NP scores of nurses comparing with NP scores of nursing students is an alarm for nursing managers and need a special attention. Keywords : Ethic, Ethical reasoning, Kohlberg, Nurses, Nursing students. * Corresponding author: Azad rahmani. PhD student in nursing education, Faculty of Nursing and Midwifery, Tabriz University of Medical Sciences, Tabriz, Iran. E-mail: azadrahmanims@yahoo.com REFERENCES -Auvinen J Suominen T Leino-Kilpi H et al (2004). The development of moral judgment during nursing education in Finland. Nurse Education Today. 24 (7) 538-546. -Bandman E Bandman B (1990). Nursing Ethics through the Life Span. Washington: Appleton & Lange Company. -Borhani F Abbaszadeh A Kohan M et al (2010). [Comparison of the moral reasoning ability of nurses and nursing students at Kerman University of Medical Sciences in dealing with ethical problems]. Journal of Medical Ethics and History. 4 (1) 74-76. (Persian) -Burnard P Chapman C (2003). Professional and Ethical Issues in Nursing, Edinburgh, Bailliere Tindall co. -Chinn PL Kramer MK (1999). Theory and Nursing: Integrated Knowledge Development. St. Louis: Mosby. -Fry S (1989). Towards a theory of nursing ethics. ANS Advances in Nursing Sciences. 11 (4) 9-22. -Fry S (2002). Defining nurse's ethical practices in the 21 st century. International Nursing Review. 49 (1) 1-3. -Ham K (2002). A comparison of ethical reasoning abilities of senior baccalaureate nursing students and experienced nurses (doctoral dissertation). The University of Memphis, United States of America. -Krawczyk R (1997). Teaching ethics: Effect on moral development. Nursing Ethics. 4 (1) 56-65. -Kelly B (1998). Preserving moral integrity: A follow up study with new graduate nurses. Journal of Advanced Nursing. 28(5) 113-45. -Ketefian S (1981). Moral reasoning and moral behavior among selected groups of practicing nurses. Nursing Research. 30(3) 171-76. -Kudzma EAC (1980). Moral reasoning of nurses in the work setting (dissertation) Massachusetts, Boston University School of Nursing. -Mayberry M (1986). Ethical decision making: A response of hospital nurses. Nursing Administration Quarterly. 10 (3) 75-81. -Murray N (1995). Moral reasoning in male and female nurses: A care perspective (dissertation). New Jersey: State University of New Jersey. -Negarandeh R Ghobadi S (2001). [Examination of knowledge and attitudes of nurses and midwives in Zanjan hospitals toward ethical issues]. Journal of Zanjan University of Medical Sciences and Health, 36, 55-58. (Persian) -Newfield S Newfield N Sperry J et al (2002). Ethical decision making among family therapists and individual therapist. Family Process. 39 (2) 177-88. -Numminen O Leino Kilpt H (2007). Nursing student's ethical decision making: A review of literature. Nurse Education Today. 27 (7) 796-801. -Pike AW (2010). I don’t know how ethical I am: An investigation into the practices nurses use to maintain their moral integrity (dissertation) Massachusetts: Boston University. -Rodney P Varcoe C Storch J et al (2002) Navigating towards a moral horizon: A multisite qualitative study of ethical practice in nursing. Canadian Journal of Nursing. 34 (3) 75-102. -Schroter K (2002). Ethic in preoperative practice- principles and application. AORN J. 75 (4) 818-24. -Schroeter K (2002). Ethics in preoperative practice- patient advocacy. AORN J. 75 (5) 941-4